HUBUNGAN TINGKAT KECERDASAN EMOSIONAL DAN KEMAMPUAN KOMUNIKASI DENGAN PROSES ADAPTASI MAHASISWA BARU DI AKADEMI KEPERAWATAN PANTI KOSALA SURAKARTA - Endang Dwi Ningsih; Fransisca Vita Febriana (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
AbstractIntroduction: Adaptation is a changing process which is individual respondtoward their environmental changing. Adaptive respond is totality respond of aperson as the holistic creature that in adaptation process the time is needed anddifferent on each other.Purpose of the study: To determine the correlation of the emotional quotientlevel and the communiation ability in adaptation process on the new student atPanti Kosala Nursing Academy.Subjects: On 103 new student at Panti Kosala Nursing Academy. Samplingtechnic used is purposif sampling, that the sampling for certain purpose.Results:Multivariat test result by â€œRegresi Logistik Gandaâ€ the value isNagelkerke R Square 45,1%Conclusion : The emotional quotient level and the communication ability bothhave significant correlation that influence to adaptation process on the newstudent at Panti Kosala Nursing Academy, the test value is 45,1% and the rest is54,9% influenced by other variable nonresearch.Keywords: The emotional quotient level, Communication ability, adaptationprocess